Proceedings of the SouthEast Conference 2017
DOI: 10.1145/3077286.3077302
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of Cloud Log Forensics

Abstract: The forensics 1 investigation of cloud computing is faced by many obstacles originating from the complex integration of technologies used to build the cloud and its sheer size. In this research we aim to provide an insight into cloud computing log forensics, as logs are an important source of forensic evidence in the cloud. This is followed with conclusions regarding the issues faced by researchers in log forensics in cloud computing that will aid the research process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Retrieval of information from log files: Log files are crucial for investigations, but gathering them from cloud computing environments is complex due to cloud haziness and multi-tenant simulations, as clients have access to the application programming interface (API) only, making monitoring impossible [ 107 ]. In the IaaS cloud model, logs are essential for understanding virtual machine (VM) behavior, but their effectiveness may be limited due to restrictions imposed by cloud providers on storage, access, or sharing among multiple users [ 108 , 109 ]. Cloud service providers often neglect or conceal log collection services, posing challenges such as decentralization, fluctuation, preservation, accessibility, non-existence, lack of important data, and non-compatible log forms [ 110 ].…”
Section: Cloud Forensic Challengesmentioning
confidence: 99%
“…Retrieval of information from log files: Log files are crucial for investigations, but gathering them from cloud computing environments is complex due to cloud haziness and multi-tenant simulations, as clients have access to the application programming interface (API) only, making monitoring impossible [ 107 ]. In the IaaS cloud model, logs are essential for understanding virtual machine (VM) behavior, but their effectiveness may be limited due to restrictions imposed by cloud providers on storage, access, or sharing among multiple users [ 108 , 109 ]. Cloud service providers often neglect or conceal log collection services, posing challenges such as decentralization, fluctuation, preservation, accessibility, non-existence, lack of important data, and non-compatible log forms [ 110 ].…”
Section: Cloud Forensic Challengesmentioning
confidence: 99%
“…Log files, one of the most crucial evidence artefacts in an investigation, must be retrieved, preserved, and maintained securely with their hash values to ensure their integrity. Research in cloud forensics has shown that log files retrieval, preservation, and maintaining the chain of custody are the primary concerns in this field [6,7,15,16].…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Digital mobile cloud forensics is the process of detecting and deducing electronic data (Zawoad & Hasan, 2013). The aim of this is to protect available proof in its novel form while undertaking a well systematic enquiry through the identification of the issue, collection of data and authentication of the electronic/digital data with the objective of reconstructing past events (Alobaidli et al, 2017). The context of this is not limited to the law court though it is most used evidentially there.…”
Section: Related Literaturementioning
confidence: 99%
“…There are enormous challenges faced by the mobile cloud forensics that have not been adequately addressed yet by scholars to find the necessary solutions for such challenges. Acquisition of data in the cloud system remains the most dominant with other different difficulties (Alobaidli et al, 2017).…”
Section: Related Literaturementioning
confidence: 99%